Vitamin A and zinc deficiencies among tuberculosis patients in Ethiopia. (August 2018) - Keflie, Tibebeselassie Seyoum; Samuel, Aregash; Woldegiorgis, Ashagrie Zewdu; Mihret, Adane; Abebe, Markos; Biesalski, Hans Konrad
Abstract: Background: The link between tuberculosis (TB) and malnutrition has long been recognized. Vitamin A and zinc deficiencies may reduce the host defenses and increase the risk for diseases. Objective: The aim of the present study was to estimate the difference in vitamin A and zinc deficiencies together with dietary intakes among pulmonary TB patients and controls. Materials and methods: A case-control study design was employed to undertake this study in North Shewa, Ethiopia. Sputum smear examination, high-performance liquid chromatography (HPLC), flame atomic absorption spectrometry (FAAS), and enzyme-linked immunosorbent assay (ELISA) were used to analyse acid fast bacilli (AFB), vitamin A, zinc, and C-reactive protein (CRP), respectively. Dietary intake was assessed using a 24-h recall questionnaire. Mann–Whitney U test, Kruskal–Wallis test, Chi-square, odds ratio (OR), Spearman correlation, and multinomial logistic regression model were computed for data analyses. Results: In this study, 62 TB cases and 59 controls were included. The proportions of vitamin A deficiency among TB cases and controls were 56.4% and 39.0%, respectively. All TB cases and 92.5% controls were zinc deficient. The odds of TB cases with deficiencies of vitamin A and zinc was 2.3 (95% CI: 1.1 to 4.8)times more likely as compared to the controls. More than 80% of all participants had below average fulfilment of energy and vitamin A intakes. Conclusion: Vitamin A and zinc deficiencies are severe problems among TB patients. Moreover, undernutrition determines the development of TB. Therefore, the management programs of TB need to address the problems of vitamin A and zinc deficiencies together with protein-energy malnutrition.